ON CERTAIN ASPECTS OF THE NATURE OF SOCIAL HUMAN RIGHTS - Сільченко, Сергій (SWorldJournal, 2025)
This article examines the nature of social human rights. Through a historical, legal, and theoretical analysis of the development of social rights, it is argued that such rights, particularly the right to social security, require not only their recognitio